2015
DOI: 10.14814/phy2.12513
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic dysfunction precedes hypoxia-induced mortality in dystrophic mice

Abstract: Duchenne muscular dystrophy (DMD) is a progressive striated muscle disease that is characterized by skeletal muscle weakness with progressive respiratory and cardiac failure. Together respiratory and cardiac disease account for the majority of mortality in the DMD patient population. However, little is known regarding the effects of respiratory dysfunction on the dystrophic heart. The studies described here examine the effects of acute hypoxia on cardiac function. These studies demonstrate, for the first time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…In the studies presented here, the mdx mouse is used to assess the pathophysiological importance of hypoxia. Recent studies have demonstrated that acute exposure of anesthetized mdx mice to hypoxia is associated with acute myocardial decompensation, characterized by initial diastolic and subsequent systolic dysfunction (65). In the present study, it is shown that this acute hypoxia-induced mortality in anesthetized mice is associated with the development of metabolic acidosis.…”
supporting
confidence: 55%
See 3 more Smart Citations
“…In the studies presented here, the mdx mouse is used to assess the pathophysiological importance of hypoxia. Recent studies have demonstrated that acute exposure of anesthetized mdx mice to hypoxia is associated with acute myocardial decompensation, characterized by initial diastolic and subsequent systolic dysfunction (65). In the present study, it is shown that this acute hypoxia-induced mortality in anesthetized mice is associated with the development of metabolic acidosis.…”
supporting
confidence: 55%
“…This observation is particularly important because of the frequency with which patients with DMD are subjected to bouts of hypoxia. Studies in anesthetized mdx mice monitoring hemodynamic function of the dystrophic heart during hypoxia exposure reveal that hypoxia-induced mortality is preceded initially by diastolic dysfunction, which transitions into a gradual decline in systolic function (65). The present studies provide important mechanistic insight into the potential causes of this hypoxia-induced mortality.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The elevation in [Ca 2+ ] i induced by hypoxia may be a common mediator contributing to cell injury in VSMCs and other tissues, such as cardiac cells and neurons. In mdx cardiac cells, acute hypoxia causes diastolic and systolic dysfunction [11].…”
Section: Clinical Considerationmentioning
confidence: 99%